Legal Dilemmas in Inclusive Education: Implementation Challenges and Teaching Strategies in Primary Schools - Putri, Arizkylia Yoka; Bimantara, Arya (Universal Education, 2025)
Inclusive education is a fundamental right guaranteed by the constitution and international conventions, ensuring that every child, including those with special needs, has access to quality education. However, despite strong legal foundations, the implementation of inclusive education in primary schools faces significant challenges. This article aims to analyze the legal dilemmas surrounding the implementation of inclusive education, the challenges faced by educators, and propose strategies for effective inclusive teaching. A literature review approach was used to examine relevant legal frameworks, existing policies, and the challenges identified in various studies. The review reveals that a lack of teacher competence in inclusive education, insufficient infrastructure, and societal stigma are major obstacles to the successful implementation of inclusive education. Additionally, regional disparities in the implementation of inclusive education further exacerbate these issues. The study suggests that teacher training programs, better resource allocation, public awareness campaigns, and more consistent policy enforcement are essential to overcoming these barriers. The findings highlight the need for coordinated efforts among policymakers, educators, and the community to ensure that inclusive education becomes a reality for all students.